THE IMPACT OF EPS, FEDERAL FUNDS RATE, PREVIOUS FEDERAL FUNDS RATE INFLATION RATE, UNEMPLOYMENT RATE, AND REAL GDP TOWARD LQ45 AND RUSSEL TOP 50 MARKET INDEX - Gymnastiar, Fahmy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to investigate the impact of microeconomics factors represented by EPS and macroeconomic factors represented by federal funds rate, inflation rate, unemployment rate and real GDP rate toward LQ45 and Russel Top 50 market indexes. In this research, the secondary data were retrieved from the official website of Indonesia Stock Exchange, Nasdaq official website, and Organisation for Economic Co-operation and Development (OECD) database. The data were analyzed with multiple regression model using SPSS application.The findings show that EPS, Federal funds target rate, Previous federal funds target rate and Inflation rate do not have a significant effect on both LQ45 and Russel Top 50 market indexes. On the other hand, unemployment rate has a negative effect on Russel Top 50 index. In contrast, unemployment rate doesn’t have significant impact on LQ45 index. Furthermore, real GDP rate has a significant effect LQ45 on market index. However, there is no significant influence on Russel Top 50 index. The negative correlation means that the decrease of unemployment rate and real GDP rate will increase the stock price